The effect of 17Î² Estradiol Exposure on Mutant p53 Expression in Hydatidiform Mole Trophoblast Cell Culture - Tatit Nurseta (Indonesian Journal of Obstetrics and Gynecology, 2011)
Objectives: To compare the mutant p53 expression in normal trophoblast (N) cell culture with hydatidiform mole trophoblast (HM) cell culture which was exposed to 17Î² estradiol. Methods: An experimental study conducted at the Laboratory of Physiology Faculty of Medicine, Brawijaya University Malang using N cell culture and HM cell culture with 17Î² estradiol exposure. Trophoblast cell culture of normal and hydatidiform mole was divided in 6 groups, such as: 1. Without added 17Î² estradiol; 2. Added 5 nm 17Î² estradiol; 3. Added 10 nm 17Î² estradiol; 4. Added 20 nm 17Î² estradiol; 5. Added 40 nm 17Î² estradiol; 6. Added 80 nm 17Î² estradiol. Then performed immunocytochemistry staining using p53 mutant primary antibody and observed the expression of p53 mutant. Data from observations analized with the ANOVA test and correlation test. Results: Mutant p53 expression in N cell culture showed no significant differences in each treatment dose of 17Î² estradiol (p = 0086 > 0.05). The dose at 80nm 17Î² estradiol showed an average of highest mutant p53 expression on N cell culture rather than giving the dose of 17Î² estradiol on 40 nm, 20 nm, 10nm and 5 nm. While the control group showed a lowest average of mutant p53 expression in N cell culture when compared to the treatment group which was exposed to 17Î² estradiol. Mutant p53 expression in HM cell culture showed a significant difference at each treatment dose of 17Î² estradiol (p = 0.000 < 0.05). The existence of the effect of 17Î² estradiol begins when the expression of mutant p53 in HM cell culture becomes higher after being given treatment in the form of 17Î² estradiol on the dose of 5 nm compared with the expression of 17Î² estradiol in the control group. Then the expression of mutant p53 in HM cell culture is increasing when given doses of 17Î² estradiol at 20 nm and 40 nm. At a dose of 40 nm it shows the highest expression of mutant p53. Expression of mutant p53 in HM cell culture decreased when given at doses 80 nm. Conclusion: Mutant p53 expression in N cell culture exposed to 17Î² estradiol showed no significant difference. Expression of mutant p53 in HM cell culture which was exposed to 17Î² estradiol showed a significant difference. Mutant p53 expression in N and HM cell culture which was exposed to 17Î² estradiol showed significantly different, in which mutant p53 expression in N cell culture is lower than the expression of mutant p53 in HM tissue culture. [Indones J Obstet Gynecol 2011; 35-1: 30-5] Keyword: p53 mutant, 17Î²-estradiol, hydatidiform mole